Induction of resistance to salinization in rape plants under the influence of elicitors derived from Pseudomonas and Bacillus bacteria - Grineva, Irina A.; Kuleshova, Yulia M.; Lomonosova, Veronica A.; Maslak, Diana V.; Sadovskaya, Ludmila E.; Skakun, Tatyana L.; Feklistova, Irina N.; Maksimova, Natalia P. (Experimental Biology and Biotechnology, 2017)
It was established that bacterial elicitors from P. chlororaphis subsp. aurantiaca 162, P. putida F19 and B. subtilis 494 are capable to increase both the seed vigor and germination of rape plants under high level of salinity condition (250 mmol/l NaCl). Сo-cultivation conditions of selected bacterial strains were optimized. The most effective elicitor’s variant capable to enhance the ability of the rape plants to generate induced systemic resistance (ISR) under salinity 150 mmol/l NaCl was selected. ISR manifested in a significant increasing of rape plants germination by 20 % and the stem length increased by 19 %. This test elicitor’s sample was prepared with heat treatment (100 °C, 15 min) of the culture broth containing P. chlororaphis subsp. aurantiaca 162 and B. subtilis 494 grown in M9 medium with molasses at 28 °C for 4 h and then at 35 °C to 48 h.